Artificial Intelligence Effect on Marketing Mix - Farouk Djermani; Hafizah Hajimia (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2021)
AI and big data to fight against the COVID-19 pandemic and review state-of-the-art solutions using these technologies. Thus, this study aimed to examine the effects of marketing mix dimensions (product, price, promotion, and place) to predict consumer behaviour, emotions and trend using AI for health care. This study will use mix method. First the qualitative research method which involved semi-structured interviews with different marketing professional belonging from different firms of Malaysia. A sample size of 10 is selected and the researcher interviewed 10 marketing professionals A quantitative approach whereby 300 questionnaires are distributed to different marketing professional from various firms in Malaysia. The analysis method used the Partial Least Square smart PLS descriptive methods. As Malaysian consumers exhibit serious concern towards to predict consumer behavior drives consumer resistance to healthcare, it is recommended that the managers focus their strategies on marketing strategies significance on to predict consumer behavior. The study discusses the implications to various stakeholders, its limitation, and recommendations for future studies.